(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
Text To Speech synthesizer plays a very important role in modern day Information Technology. Communication technology can be enhanced by speech technology to a greater extent. There are a number of steps in natural language processing phase of a Text to speech synthesizer. In this paper the approach to make a TTS for Indian language is shown by taking Assamese as an example. First explanation is how to get lexicons of the language then an idea of using DONLabel tool is shown. To build a speech synthesizer for any language, researcher should acquire adequate knowledge about the phonetic and acoustic characteristic of that language. In this research paper important features of Indian languages, the proposed block diagram for synthesis process, preparation of lexicons from the written text for Assamese language is explained with snapshots.